On the frontlines gender, war, and the post-conflict process - d; Haynes, Dina Francesca; Cahn, Naomi R. (New York : Oxford University Press, 2011)
Today, in a variety of post-conflict settings international advocates for women's rights have focused on bringing issues of sexual violence, discrimination and exclusion into peace-making processes. 'On the Frontlines' consider such policies and assess the extent to which they have had success in improving women's lives.
Also issued in print format.
Description based on online resource; title from PDF title page (viewed on Jan. 20, 2012).
Includes bibliographical references and index.
Keywords: Women and war; Women and peace; Women -- Violence against; Sex discrimination against women; Women's rights; Postwar reconstruction